A Study of Efficiency of the Indian Stock Market - Iqbal; Mallikarjunappa, Dr. T. (Indian Journal of Finance, 2010)
Market efficiency is examined in three forms: weak form, semi-strong form and strong form and each one deals with a different source of information. 1. Weak form efficient market - the prices of securities fully reflect all historical information and no excess returns can be earned by utilising historical share prices. 2. Semi-strong form - securities prices adjust instantaneously to available new information such as earnings announcements, bonus issue, merger and acquisition, etc. so that no excess returns can be earned by trading on that information. 3. Strong form efficient market - securities prices fully reflect all information, including inside or private information.